An analysis of the training programs of the library associations in the Philippines, 1999-2008 a follow-up study - Mendoza, Ethel H. (2010)
Library associations help educate and empower professionals about the new library development and assist information professionals in providing and invaluable informal setting for information sharing, updating and improving their skills. Thus, the main purpose of this study is to analyze and evaluate the training programs of nine national library associations and provide data that would help explain how these associations go about with their training seminars and conferences.